Pengaruh Likuiditas Dan Perputaran Modal Kerja Terhadap Profitabilitas Pada PT Smart Tbk. Periode Tahun 2011-2019 - Nur Annisa Oktaviani Sofyan; Richad Alamsyah (Institut Bisnis dan Informatika Kesatuan, 2021)
The development of the era of globalization has made the business world in Indonesia continue to grow so that it has increased significantly from year to year. This is an attraction that spurs investors to invest their capital, especially with the implementation of free trade which encourages investors to take business units in various parts of the world or become new competitors in similar industries. Competition that occurs requires companies to be more competitive so as not to lose to compete with other companies. Therefore, to maintain the survival of the company and generate optimal profits, the company must be able to manage its finances well, meaning that financial management policies must be able to ensure the company's business continuity, by increasing all company activities and optimizing the resources they have properly. must be smart and fast in taking appropriate steps to anticipate the development of the business world with productivity competitiveness based on production efficiency and effectiveness. This study aims to obtain findings about (1) the effect of liquidity and working capital turnover partially on profitability, (2) the effect of liquidity and working capital turnover simultaneously on profitability. The type of data used in this study is secondary data, namely the quarterly financial statements of PT SMART Tbk for the period 2011-2019. The analysis used in this study is multiple linear regression analysis using the Statistical Package for Social Sciences (SPSS) version 25 program. The total sample used by the author is 36 data. The results showed that liquidity had an effect on profitability. Working capital turnover has no effect on profitability. Liquidity and working capital turnover together have a positive effect on company profitability. Keywords: Liquidity, Working Capital Turnover, Profitability